(untitled) (Journal of Renal and Hepatic Disorders, 2020)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. Chronic liver disease due to viral hepatitis, alcohol, non-alcoholic fatty liver disease, etc are risk factors for HCC development. Triphasic contrast-enhanced computed tomography (CECT) and magnetic resonance imaging (MRI) abdomen are modalities for HCC diagnosis best for lesions >2 cm size. For lesions <2 cm size, liquid biopsy with the determination of cell-free DNA in the blood is a newly emerging technique for diagnosis as well as for the planning of molecular targeted therapy. With the new concept of “Treatment stage migration”, the updated Barcelona clinic liver cancer (BCLC) algorithm for HCC management allows the best treatment modality for an individual patient. In addition to definitive therapy of resection and liver transplantation, palliative therapies like ablation, transarterial embolization, and others can be used. Among molecular targeted therapies for advanced BCLC stage C HCC, lenvatinib as first line, regorafenib and cabozantinib as second line therapy have been approved recently. The checkpoint inhibitors (CPIs), nivolumab and pembrolizumab, have revolutionized oncology practice in other solid organ cancers and have shown promising results in HCC management.